A copper hexacyanocobaltate nanocubes based dopamine sensor in the presence of ascorbic acid. Issue 54 (17th May 2016) - Karikalan, N.; Velmurugan, M.; Chen, S. M.; Chelladurai, K.
Abstract : A highly selective and sensitive dopamine sensor was demonstrated based on copper hexacyanocobaltate nanocubes in the presence of ascorbic acid. Abstract : A novel copper hexacyanocobaltate based sensor was developed and its electrocatalytic behavior towards the oxidation of dopamine (DA) was demonstrated. Among the Prussian blue analogues, copper hexacyanocobaltate (CuHCC) exhibits unique electrochemical responses due to its bimetallic combination of copper and cobalt. As-prepared CuHCC shows a well-defined cubic structure with an average size of around 252 nm, which was confirmed by XRD and FE-SEM. Raman spectroscopy confirmed the coordination behavior of both the metal and ligand in CuHCC, which existed as Co III –CN–Cu II and Co II –CN–Cu III . The as-prepared CuHCC was used for the first time in DA detection and provided a better platform as a DA sensor. The electrocatalytic activity of CuHCC towards dopamine was examined by cyclic and differential pulse voltammetry. The CuHCC fabricated sensor shows a wide linear range from 0.1 to 350 μmol L −1 and low detection limit of 19 nmol L −1 . The sensor reported herein displays excellent sensitivity, high stability and appreciable reproducibility for DA oxidation.